Modeling developmental changes in print tuning in a transparent alphabetic orthography - Verhoeven, Ludo; Voeten, Marinus; Keuning, Jos (Frontiers in Neuroscience, 2022)
The development of word decoding involves the increased specificity and redundancy for orthographic representations. However, it is by no means clear how decoding accuracy and efficiency are related over the years and how it affects reading disability. In the present study, we monitored the development of accuracy and efficiency of decoding in Dutch as a relatively transparent orthography as a function of orthographic complexity and lexical status throughout the primary grades. There was clear evidence that development of reading accuracy preceded development of reading efficiency and that a certain threshold of accuracy is needed for reading efficiency to evolve. Furthermore, it was shown that pseudoword reading efficiency predicted growth in word reading efficiency, especially for the higher levels of orthographic complexity. There was also evidence that accuracy precedes efficiency across different profiles of readers and that decoding strength can be defined as a function of orthographic complexity and lexicality.